Religion, Religiosity, and the Moral Divide in Canadian Politics - Ang, Adrian (Politics and religion, 2012)
Social group conflict along regional, ethnic, linguistic, and religious cleavages is deeply embedded in the Canadian historical experience. Contemporary analyses, however, have deprecated the role of religion and religiosity in shaping Canadians' political attitudes. This analysis demonstrates that religion and religiosity are significant correlates of Canadian attitudes on moral issues, paralleling the pattern observed in the United States. It demonstrates that the religious cleavage has been a salient feature of Canadian politics for some time and considers whether the contemporary moral divide could serve as a portent of cultural-religious conflict in Canada if a "political entrepreneur" articulated an issue agenda linked to these religion-based differences.